Estimation of mass, cosmological constant and Kerr parameter of different galaxies using geodesic motion in Kerr-de Sitter space-time - Poudel, PC; Khanal, U (Scientific World, 2012)
In the present work, geodesic trajectories in Kerr-de Sitter geometry is used to fit the rotation curve of galaxies and estimate the values of mass M, Kerr parameter a, and cosmological constant Ë. In this work, non-linear least square fitting of rotational velocity is used to estimate the some of the parameters. These estimates are mass in the range of (0.12±0.02) x1010 M to (70.37±11.26) x1010 M, the Kerr parameter in the range of (0.7044±0.1127) to (0.9990±0.1598), and the cosmological constant in the range of (1.790±0.286) x10-49 km-2 to (7.523±1.204) x10-42 km-2 for positive value of Ë while - (3.983±0.637) x10-41 km-2 to - (1.860±0.298) x10-42km-2 for negative value of Ë. The negative Ë values are found only for some galaxies with large recessional velocity. This suggests that the transition from anti-de-Sitter to de-Sitter phase with the deposition of vacuum energy may have occurred between the formation of these different galaxies. Scientific World, Vol. 10, No. 10, July 2012 DOI: http://dx.doi.org/10.3126/sw.v10i10.6852